A Non-Enzymatic Electrochemical Sensing Platform Based on Hemin@MOF Composites for Detecting Hydrogen Peroxide and DNA. Issue 16 (21st December 2018) - Cheng, Dan; Xiao, Xuelian; Li, Xi; Wang, Chen; Liang, Yani; Yu, Zhengsong; Jin, Chenglong; Zhou, Nan; Chen, Ming; Dong, Yulin; Lin, Yawei; Xie, Zhizhong; et al.
Abstract : In this work, Hemin@MOF was prepared by doping hemin into Cu-MOF-199 and applied in the electrochemical sensing of H2 O2 and DNA. The Hemin@MOF modified electrode (Hemin@MOF/GCE) exhibited an excellent electrocatalytic activity toward H2 O2 and the detection limit of H2 O2 was as low as 0.07 μmol·L −1 with the range of 0.1 to 2200 μmol·L −1 . Based on the eminent electrochemical performance, Hemin@MOF was further employed as an electrochemical signal indicator to construct a novel electrochemical DNA biosensor. Here, via amidation reaction, the stem-loop-structure probe DNA (pDNA) carrying 3'-amino and 5'-biotin was anchored on the carboxyl functionalized graphene. Then the pDNA was unfolded by the hybridization of the matched target DNA (tDNA). The following recognition between streptavidin (SA) on the Hemin@MOF-SA and biotin at the pDNA led the Hemin@MOF-SA to access the electrode surface. In this way, the electrode modified with Hemin@MOF-SA and matched tDNA could display remarkable catalytic activity toward the reaction of H2 O2 . The proposed electrochemical DNA biosensor showed an excellent performance with 9 orders of magnitude in the range from 1.0 × 10 −15 to 1.0 × 10 −6 mol·L −1, the low detection limit of 6.9 × 10 −16 mol·L −1 and the one-base mismatch differentiation ability. In addition, the two as-prepared electrochemical sensors also exhibited good stability, showing a potential application in the practical analysis.